The New Zealand coaching strategy (Sport & Recreation New Zealand, 2007)
Strategy Objectives Implementation Principles World-Class Coaching Environment - Implementation Plan Building Coaching Communities - Game Plan Creating the Coaching Environment - Game Plan Appendix One - Key Players Appendix Two - Current Activities